AN ELEMENTARY PROOF OF FISHER-COCHRAN THEOREM USING A GEOMETRICAL APPROACH - CHAVES, Lucas Monteiro; SOUZA, Devanil Jaques de (Brazilian Journal of Biometrics, 2019)
The classical Fisher-Cochran theorem is a fundamental result in many areas of statistics as analysis of variance and hypothesis tests. In general this theorem is proved with linear algebraic arguments. An elementary proof is present, based strongly on geometrical concepts as linear subspaces and orthogonal projections, which may improve our intuition about the result.